Arte urbana no capitalismo em chamas: pixo e grafite em explosão - Santos, Juliana Abramides dos (2019)
In the 21st century, the most widespread art is not being produced by the great art centers and elitist, bourgeois and aristocratic groups but has been created by young people and adults who proclaim territorial identities while marking visible surfaces. The main plastic aspect in the world today is the aesthetics of the periphery and manifests itself differently as an expression of urban, artistic and cultural resistances to the burning capitalism